Sistem Informasi Inventory Control Lovia Jambi - Afrizal, Afrizal (Lembaga Penelitian Dan Pengabdian Masyarakat - STMIK Nurdin Hamzah Jambi, 2016)
The utilization of information technology becomes a necessity that is used to improve or assist the performance of the company. Every company seeks to build a system that can assist and facilitate its performance. This paper describes the stages in building an information system inventory in the warehouse Lovia Jambi to assist and facilitate the operations conducted by the warehouse, provide information faster, accurate and relevant, minimize errors such as the difference between the amount of goods and facilitate the search the data if necessary, to save time in data processing, report generation goods in and goods out can be done easily and quickly. This information system built using Visual Basic 6.0 programming language and MySQL datababe.